A positive notion of power for citizen voice and state accountability. Issue 6 (17th August 2016) - Winterford, Keren
ABSTRACT: This article explores the notion of power within citizen–state relations. A positive notion of power is presented as an addition to evolving development discourse which has predominantly defined power as a finite resource transferred from state to citizen in a process of ''changing the balance of power''. A positive notion of power is concerned with maximising and connecting citizen power and affirming state power, for synergistic change. The article draws on development discourse and practical examples to outline a positive notion of power, prioritising relational dialogue and joint citizen state action for development outcomes.